(untitled) (Central Asian Journal of Medical Sciences, 2021)
Objective: Develop and validate a novel, sensitive, precise and straightforward UV spectrophotometric method to determine the amount of dioscin in tribulmon tablets. Methods: tribulmon tablets were prepared in the laboratory from medicinal plants Tribulus Terrestris L, native to Mongolia. Extract solutions were prepared from a single batch of tribulmon tablets, and the amount of dioscin was determined by UV spectrophotometric method using a calibration curve of known solutions of the dioscin. A chromogenic reaction was used to determine the amount of dioscin in the tablets. The maximum absorption was 201 nm. Validation parameters were evaluated following ICH guidelines. Results: The correlation coefficient of linearity for the UV spectrophotometric method was 0.9996. The standard working solution was linear from 3.2 to 18.9 μg/mL. The Limit of Detection (LOD) and Limit of Quantitation (LOQ) were 1.9 μg/ mL and 5.9 μg/mL, respectively. The recovery test accuracy was ranged from 97.9 to 100%. The %RSD for repeatability and intra-day precision was 0.45%, 0.13–0.50%, respectively. The %RSD for robustness was 0.26% to 0.40%, respectively. Conclusion: Based on the results of the proposed UV spectrophotometric method, the method we developed to determine dioscin content in tribulmon tablets from Tribulus Terrestris L is sensitive, precise, stable and straightforward. The test’s validation parameters comply with ICH requirements.